Nonparametric Identification and Estimation of Multi-Unit, Sequential, Oral, Ascending-Price Auctions With Asymmetric Bidders - Harry J. Paarsch; Bjarne Brendstrup (Fondazione Eni Enrico Mattei (FEEM), 2004)
Within the independent private-values paradigm, we derive the data-generating process of the winning bid for the last unit sold at multi-unit sequential English auctions when bidder valuations are draws from different distributions; i.e., in the presence of asymmetries. When the identity of the winner as well as the number of units won by each bidder in previous stages of the auction are observed, we demonstrate nonparametric identification and then propose two estimation strategies, one based on the empirical distribution function of winning bids for the last unit sold and the other based on approximation methods using orthogonal polynomials. We apply our methods to daily data from fish auctions held in Grenå, Denmark. For single-unit supply, we use our estimates to compare the revenues a seller could expect to earn were a Dutch auction employed instead.
Keywords: C14; D44; L1; Q22; 330; Asymmetric; Multi-unit; Sequential; Oral; Ascending-price fish auctions; Dutch auctions; Nonparametric identification and estimation; Auktionstheorie; Nichtparametrisches Verfahren